Beginning iOS game center and game kit for iPhone, iPad and iPod Touch - Richter, Kyle (Apress Distributed to the book trade worldwide by Springer Science+Business Media, 2011)
Beginning iOS Game Center and Game Kit shows you how to use Game Center and Game Kit to create fun and polished games that use advanced features such as social networking and voice over IP (VoIP). Game Kit and Game Center can help you reach new customers through social interaction, so this book shows you how you can quickly add a level of polish to your app that used to take weeks of hard work and late nights. Implementing a leaderboard and achievement system has never been so simple! Gone are the days of writing your own server. You'll also see how to easily add advanced networking concepts like VoIP support in hours, not days. Learn how to quickly implement many advanced social networking concepts into your apps. You'll be guided through the process of creating a custom Game Center Manager class that can be rapidly deployed into any of your new or existing projects. Furthermore, learn how to avoid pitfalls commonly encountered by new Game Center developers.